Problematic issues of the evolution of pre-revolutionary cooperative legislation in Russia - A. V. Chichulin (Омский научный вестник: Серия "Общество. История. Современность")
The article reveals problematic issues related to the process of formation and development of pre-revolutionary Russian cooperative legislation. The main stages of legislative support for the development of cooperative organizations and their unions are identified. The nature and degree of administrative influence of various state authorities on the cooperative movement in the pre-revolutionary period is determined. Problematic moments associated with collisions of cooperative legislation that interfere with the effective functioning of the cooperative system in Russia are identified.